Promises and Pitfalls of NMDA Receptor Antagonists in Treating Violent Aggression - Bartsch, Caitlyn J.; Nordman, Jacob C. (Frontiers in Behavioral Neuroscience, 2022)
Treatment options for chronically aggressive individuals remain limited despite recent medical advances. Traditional pharmacological agents used to treat aggression, such as atypical antipsychotics, have limited efficacy and are often replete with dangerous side effects. The non-competitive NMDAR antagonists ketamine and memantine are promising alternatives, but their effects appear to be highly dependent on dosage, context, and personal experience. Importantly, these drugs can increase aggression when combined with substances of abuse or during periods of heightened stress. This is likely due to mechanistic differences operating at specific synapses under different contexts. Previous findings from our lab and others have shown that early life stress, substance abuse, and attack experience promote aggression through NMDAR-dependent synaptic plasticity within aggression neurocircuits. Ketamine and memantine affect these types of aggression in opposite ways. This has led us to propose that ketamine and memantine oppositely affect aggression brought on by early life stress, substance abuse, or attack experience through opposite effects on NMDAR-dependent synaptic plasticity. This would account for the persistent effects of these drugs on aggression and suggest they could be leveraged as a more long-lasting treatment option. However, a more thorough examination of the effects of ketamine and memantine on cellular and synaptic function will be necessary for responsible administration. Additionally, because the effects of ketamine and memantine are highly dependent on prior drug use, traumatic stress, or a history of aggressive behavior, we propose a more thorough medical evaluation and psychiatric assessment will be necessary to avoid possible adverse interactions with these drugs.